Characterising diversity of rural farm households in Eastern Africa: implications for food security and intra-household decision-making - Henderson, Adelaide; Barnes, Andrew P.; Hammond, James (Frontiers in Sustainable Food Systems, 2024)
The heterogeneity in East African small-holder agricultural systems influences the farm households’ welfare outcomes. We examine the heterogeneity of rural farm households in Eastern Africa and the influence of such diversity on household food security and how these relate to intra-household decision-making dynamics. Using data from the Rural Household Multi-Indicator Survey (RHoMIS) 1,199 households in Ethiopia, Kenya, Malawi and Uganda were typologized using partition-based cluster analysis. These were grouped into relatively homogenous classes reflecting their socio-demographic characteristics, resource endowment and farm orientation based at a country level to reflect the unique institutional conditions within these countries. Additional analysis was then used to characterise the differences in food insecurity and intra-household decision-making of these clusters. Five distinct farm household clusters were identified in Ethiopia and Kenya, four in Malawi and three in Uganda. The main factors differentiating the farm clusters were educational attainment of the household head, levels of resource endowment, market orientation and off-farm income. Market orientated clusters and clusters comprising more educated household heads were generally more food secure across all countries. In Ethiopia, Kenya and Uganda, women had greater decision-making control in clusters comprising least educated household heads. Female decision-making control was negatively associated with the resource endowment of clusters in Kenya, Malawi and Uganda. This emphasises the importance of understanding rural farm household heterogeneity when tailoring interventions to target household food insecurity and gender inequity in decision-making in Eastern Africa.